Intervenções de terapia de comportamento temporomandibular transtornos: uma revisão sistemática - Mouta Neto, José Ângelo (2017)
Temporomandibular disorders, which are the major cause of non -dental pain in orofacial region, encompasses a group of musculoskeletal and neuromuscular conditions involving temporomandibular joints (TMJ), masticatory muscles, and all associated tissues. Orofacial pains are highly prevalent and debilitating conditions involving the head, face and neck. They can be defined as pain in the face, mouth and/or jaw and involve temporomandibular dysfunction, atypical facial pain, facial neuralgia, and others. The incidence of temporomandibular dysfunction i s 4% per a nnum, which is considered quite high. One of the common therapeutic indications for orofacial pain is behavior therapy, a set of psychological interventions aimed at producing new behaviors that have the outcome of relief or reduction of pain. The present study had as objective to seek the evidences of the behavioral therapy in pain relief for the cases of temporomandibular disorders. A systematic review of randomized clinical trials was used as method. We searched the databases Pubmed, PsycINFO, LILACS , Scielo, IBECS, CUMED, BBO -Odontologia, MedCarib and Homeoindex, as well as gr ey literature (literature not officially published) on databases OpenGrey and ClinicalTrials.gov. We included randomized clinical trials of behavioral therapy interventions for orofacial pain that produced relief or reduction of pain. The protocol for this systematic review was elaborated based on PRISMA-P and registered in PROSPERO (registration number: CRD42017069948). The results indicated that there are 26 randomized clinical trials (RCTs) on behavioral t herapy for Temporomandibular Dysfunction, 4 RCTs on bruxism, 2 on persistent idiopathic pain and 1 on oral burning syndrome. The majority of Behavior Therapy interventions were CognitiveBehavioral Therapy (n = 18), followed by Relaxation Techniques (n = 6), Biofeedack (n = 5) and Habit Reversal (n = 3). Results are heterogeneous, but demonstrate the efficacy of behavioral interventions for orofacial pain, especially Cognitive -Behavioral Therapy for TMD. It is concluded that behavior therapy interventions are important for orofacial pain, especially for TMD, and may be provided by health professionals as a way to improve care and management of pain symptoms.